Bioelectrochemical reduction of volatile fatty acids in anaerobic digestion effluent for the production of biofuels. (15th December 2015) - Kondaveeti, Sanath; Min, Booki
Abstract: This study proves for the first time the feasibility of biofuel production from anaerobic digestion effluent via bioelectrochemical cell operation at various applied cell voltages (1.0, 1.5 and 2.0 V). An increase in cell voltage from 1 to 2 V resulted in more reduction current generation (−0.48 to −0.78 mA) at a lowered cathode potential (−0.45 to −0.84 mV vs Ag/AgCl). Various alcohols were produced depending on applied cell voltages, and the main products were butanol, ethanol, and propanol. Hydrogen and methane production were also observed in the headspace of the cell. A large amount of lactic acid was unexpectedly formed at all conditions, which might be the primary cause of the limited biofuel production. The addition of neutral red (NR) to the system could increase the cathodic reduction current, and thus more biofuels were produced with an enhanced alcohol formation compared to without a mediator. Graphical abstract: Highlights: Anaerobic digestion effluent was used for biofuel production via bioelectrochemical reduction. Various forms of bioalcohols and biogases were recovered from anaerobic digestion effluent. The main bioalcohols in bioelectrochemical reduction were butanol, ethanol, and proponol. Supplementation of mediator to the system enhanced reductive current and biofuels production.